How personal music preference and SES affect substance use among university students - Guðmar Bjartur Elíasson 1994- (2020)
The association between substance use (illicit substances, alcohol, tobacco), personal music preference and socioeconomic status (SES) was examined among Icelandic university students. Rap/Hip-hop music was expected to the musical preference most associated with substance use. Participants with low SES scores were also expected to report higher substance use. The University of Reykjavik assisted in collecting data. A total of 289 students took part in the online survey distributed via email. The participants, of which 139 (56.3%) were women and 109 (43.7%) were male, were on the ages of 18 to 36 years or older when the study was conducted. Pop/RnB music turned out to be the most popular music preference among the participants. To examine the association between variables the spearman correlation coefficient and crosstabs were used. The results demonstrated a strong association between listening primarily to electronic music and using illicit substances known as club- drugs, such as MDMA, LSD, ecstasy and cocaine. Primarily listening to Pop/RnB music was consistently negatively associated with substance use. That association was significant with marijuana and cocaine use. The results also indicated a weak negative association between SES and illicit substance use. Indicating that as SES lowers the illicit substance use increases. Sambandið milli fíkniefnanotkunar (ólögleg fíkniefniefnanotkun, áfengisnotkun, tóbaksnotkun) persónulegs tónlistarsmekks og félagslegrar stöðu (SES) var rannsakað meðal íslenskra háskólanema. Reiknað var með því að Rapp/Hip-Hop tónlist yrði sú tónlistarstefna sem yrði mest tengd við notkun fíkniefna. Einnig var búist við því að þátttakendur með lægri SES myndu tilkynna meiri notkun fíkniefna en aðrir. Gagnasöfnun var unnin með Háskólanum í Reykjavík sem sendi út rafrænan spurningalista. Alls voru þátttakendur 289. Þar af voru 139 (56.3%) kvenkyns og 109 (43.7%) karlkyns. Þátttakendur voru á aldrinum 18 til 36 ára og eldri. Algengast var að þátttakendur hlustuðu aðallega á Rokk. Til að ...